Employees' job behavior and attitude :the impact of power bases - Chin, Lee Min (Universiti Malaysia Sarawak, 2005)
This present study attempts to bridge the gap by the impact of power bases on employees' job satisfaction, absenteeism,and turnover intention within the manufacturing firms in Malaysia. This study gives attention to seven power bases known as legitimate, coercive, reward, expert, referent, informational, and connection power.